2017
DOI: 10.1016/j.radcr.2017.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Huge traumatic pulmonary artery pseudoaneurysm

Abstract: Pulmonary artery pseudoaneurysm is a very rare complication of penetrating thoracic trauma. We present a case of a 27-year-old woman who developed a 6.5-cm traumatic pulmonary artery pseudoaneurysm after suffering multiple stab wounds to the chest and the abdomen. The pseudoaneurysm was successfully treated endovascularly with vascular plug occlusion and coil embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The main causes represented in our recent literature review were infective (36.7%), paraneoplastic (31.8%), Swan-Ganz-induced (13.6%), traumatic (9%), post-surgical (4.5%), and iatrogenic (4.5%) [7][8][9][10][11][12][13][14][23][24][25][26]31,32,44,[54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 94%
“…The main causes represented in our recent literature review were infective (36.7%), paraneoplastic (31.8%), Swan-Ganz-induced (13.6%), traumatic (9%), post-surgical (4.5%), and iatrogenic (4.5%) [7][8][9][10][11][12][13][14][23][24][25][26]31,32,44,[54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 94%
“…Patients feel pain when their tissues are damage. A study reported that pain was divided into acute and chronic persistent pain according to the pain time [5]. Pain can be divided into neuropathic and nociceptive pain.…”
Section: Discussionmentioning
confidence: 99%
“…[ 43 ] Traumatic pulmonary artery pseudoaneurysms (PAPs) are rare, with around 30 cases reported in the literature. [ 50 , 51 ] Unlike systemic arterial PSAs, which enhance the arterial phase, PAPs are focal rounded areas of the contrast pool that corresponds to the pulmonary arterial enhancement. [ 52 ] Patients with chest pain, dyspnea, and hemoptysis can be managed through interventional techniques such as percutaneous hemostatic ablation or coil angioembolization and ultimate lung resection.…”
Section: Penetrating Injuries To the Chestmentioning
confidence: 99%